Measuring the extent to which consumers are aware of the label on food commodities and its relationship to consumer awareness (An exploratory study of the opinions of a sample of consumers in Baghdad Governorate) (Journal of the College of Basic Education, 2022)
The research aims to identify the extent to which the Iraqi consumer understands and comprehends the information contained in the label indicating food commodities and to identify the variables related to consumer awareness, as well as to test the relationship between personal variables and the degree of consumer awareness. It reached (243) people in the Baghdad governorate and in the districts of Karkh and Rusafa, and their responses were analyzed using weighted arithmetic means and percentile weights, as well as using the Spearman correlation coefficient to test the relationship between consumer awareness and personal variables.